(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Disaster preparedness and response are integral components of public health, with nurses playing a pivotal role in protecting community health during emergencies. This paper examines the multifaceted contributions of nurses in disaster management, highlighting their roles in emergency care, public education, disaster planning, and community health assessment. Nurses provide critical emergency care on the front lines, offering immediate medical interventions, triaging patients, and coordinating response efforts. Through public education and outreach initiatives, nurses empower communities to prepare for disasters, mitigate risks, and respond effectively. In disaster planning and management, nurses collaborate with interdisciplinary teams to develop response plans, allocate resources, and coordinate healthcare services. Additionally, nurses conduct community health assessments to identify health needs, prioritize interventions, and advocate for policies that promote resilience. Through their expertise, compassion, and leadership, nurses enhance the effectiveness of disaster response efforts and contribute to building more resilient communities capable of overcoming adversity.